Noise Trading, Transaction Costs, and the Relationship of Stock Returns and Trading Volume - Kramer, Charles (IMF Working Papers; Working Paper ;, 1994)
The relationship of stock returns and trading volume is the focus of much recent interest. I examine an economic model of a rational trader who operates in a market with transactions costs and noise trading. The level of trading affects the rational trader's marginal cost of transacting; as a result, trading volume is a source of risk. This engenders an equilibrium relationship between returns and volume. The model also provides a simple way to scrutinize this relationship empirically. Empirical evidence supports the implications of the model.